2019
DOI: 10.3892/etm.2019.8358
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of TOR signaling pathway regulator suppresses cell migration and invasion in non‑small cell lung cancer via the regulation of epithelial‑to‑mesenchymal transition

Abstract: Non-small cell lung cancer (NSCLC) is one of the most common cancer types worldwide. Previous studies have indicated that TOR signaling pathway regulator (TIPRL) is involved in the progression of NSCLC. However, the underlying mechanisms of the role of TIPRL in regulating NSCLC metastasis have remained largely elusive. In the present study, the expression pattern of TIPRL in NSCLC was analyzed using The Cancer Genome Atlas (TCGA) dataset. Furthermore, Kaplan-Meier curve analysis was performed to evaluate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…TIPRL expression was increased in NSCLC tissues in comparison to normal tissues, and TIPRL could contribute to autophagy so as to facilitate NSCLC development through the eukaryotic initiation factor 2α (eIF2α)-Activating Transcription Factor 4 (ATF4) pathway [ 23 ]. In addition, TIPRL was found to correlated with lower overall survival rate of NSCLC patients; TIPRL knockdown suppressed NSCLC metastasis, indicating that TIPRL acted as an oncogene in NSCLC [ 36 ]. Similarly, our data also showed that TIPRL was upregulated in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…TIPRL expression was increased in NSCLC tissues in comparison to normal tissues, and TIPRL could contribute to autophagy so as to facilitate NSCLC development through the eukaryotic initiation factor 2α (eIF2α)-Activating Transcription Factor 4 (ATF4) pathway [ 23 ]. In addition, TIPRL was found to correlated with lower overall survival rate of NSCLC patients; TIPRL knockdown suppressed NSCLC metastasis, indicating that TIPRL acted as an oncogene in NSCLC [ 36 ]. Similarly, our data also showed that TIPRL was upregulated in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Using the same model, Zheng revealed that 160 mg/kg baicalin administration significantly alleviated kidney damage, metabolic disorders and renal fibrosis by anti-inflammatory and anti-oxidative stress mechanisms. Zheng’s results suggested that baicalin inhibits inflammation through the NF-κB signalling pathway, blocks extracellular matrix accumulation through the TGF-β/Smad3 pathway, and regulates cell proliferation via the insulin-like growth factor (IGF)-1/IGF-1 receptor/p38 mitogen-activated protein kinase (MAPK) pathway [ 48 ].…”
Section: Flavonoids For the Treatment Of Diabetic Nephropathymentioning
confidence: 99%
“…Lung cancer diagnoses numbered 228,000 in the United States in 2019 with around 160,000 deaths ( 17 ), demonstrating the disease has a high incidence, high fatality rate, and a poor prognosis. Lung adenocarcinoma is the most prevalent form of NSCLC ( 18 , 19 ), and determining its mechanism of incidence, invasion, and metastasis.…”
Section: Discussionmentioning
confidence: 99%